1992
DOI: 10.1073/pnas.89.2.623
|View full text |Cite
|
Sign up to set email alerts
|

Possible influences on the expression of X chromosome-linked dystrophin abnormalities by heterozygosity for autosomal recessive Fukuyama congenital muscular dystrophy.

Abstract: Abnormalities of dystrophin, a cytoskeletal protein of muscle and nerve, are generally considered specific for Duchenne and Becker muscular dystrophy. However, several patients have recently been identified with dystrophin deficiency who, before dystrophin testing, were considered to have Fukuyama congenital muscular dystrophy (FCMD) on the basis of clinical findings. Epidemiologic data suggest that only 1/3500 males with autosomal recessive FCMD should have abnormal dystrophin. To explain the observation of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Examples include the interaction of a and 3 tubulin mutations in Drosophila'06 and, more speculatively, the enhanced severity of dystrophin mutations in trans to an abnormal allele for autosomal recessive Fukuyama congenital muscular dystrophy. 107 An allied phenomenon, called negative complementation or metabolic interference, occurs when two alleles at the same locus interact to give a more severe phenotype in the compound heterozygote than in either homozygote. For example, Abruptex (Abx) mutations of the Drosophila Notch gene fall into two genetic types, "enhancers" and "suppressors" of Notch.…”
Section: Dominant Negative Mutationsmentioning
confidence: 99%
“…Examples include the interaction of a and 3 tubulin mutations in Drosophila'06 and, more speculatively, the enhanced severity of dystrophin mutations in trans to an abnormal allele for autosomal recessive Fukuyama congenital muscular dystrophy. 107 An allied phenomenon, called negative complementation or metabolic interference, occurs when two alleles at the same locus interact to give a more severe phenotype in the compound heterozygote than in either homozygote. For example, Abruptex (Abx) mutations of the Drosophila Notch gene fall into two genetic types, "enhancers" and "suppressors" of Notch.…”
Section: Dominant Negative Mutationsmentioning
confidence: 99%
“…The deletion of exons 51–54 of dystrophin is predicted to cause an out of frame splicing of exon 50 to exon 55, resulting in the absence of the dystrophin protein which should cause a severe form of DMD as reported. 12 DC was observed in patients with gross deletions of the dystrophin gene mainly deletions of exons 48–49. 3 13 14 Deletions in exons 48, 45 to 53, and 49 have also been reported to cooccur with cardiomyopathy in some of the cases; 15 16 but the connection between the cardiac phenotype to the dystrophin genetic composition was not established.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the high frequency of dystrophin de¢ciency in males with Fukuyama muscular dystrophy, it has been suggested that the Fukuyama muscular Table 3. Some mechanisms for the phenotypic diversity of thalassaemia heterogeneity of mutations at the b-globin gene locus action of modi¢ers primary: a-globin genes; g-globin genes secondary: multiple loci, involving bone, iron and bilirubin metabolism; others variability due to co-selection acquired factors environment geographical, social, cultural dystrophy gene product normally interacts with dystrophin, and that the phenotype in these severely a¡ected males re£ects heterozygosity for the Fukuyama mutation coupled with a DMD gene mutation (Beggs et al 1992). Retinitis pigmentosa is the name given to a set of inherited degenerations of the retina.…”
Section: Phenotype±genotype Relationships For Other Monogenic Diseasesmentioning
confidence: 99%